Research Monogram No. 3, "Local Government Financial Management and Accounting: A Research Framework" (Book). - Hendrickson, Harvery S.; Prentice, Charles A. (The Accounting Review, 1984)
Abstract Reviews the book,"Local Government Financial Management and Accounting: A Research Framework," by Katherine Graham.